Nilai-nilai Pendidikan dalam Hikayat Akhbarul Karim (Analisis Relevansi Kurikulum) - Muhibuddin Muhibuddin (DAYAH: Journal of Islamic Education, 2020)
Muslim religious leaders play very important role in speeding the progress of education and knowledge in Aceh. One of the roles done by them is writing historical script. One of the manuscript, Akhbarul Karim (nobel news), created by the most famous muslim religious leader and used to be wellknown for one decade 1860-1960 was composed by Teungku Syekh in Seumatang Geudong. The study of the manuscript of Akhbarul Karim is needed in order to bring up all information about value of Islamic religion education. In general, the problems that will be solved on this research are as following. Firstly, what kind of education value is contained in manuscript Akhbarul Karim?. Secondly, what is the relevance between the education value which is contained in manuscript Akhbarul Karim and 2013 curriculum material?. Technical analysis used by the writer is content analysis. Based on the analysis carried on, the writer found several Islamic education value contained in Akhbarul Karim manuscript created by Teungku Seumatang: (a) faith value (b) act of devotion value (c) moral value. The three values are extended on each sentences in that manuscript and they have relevance with faith, moral and religious service in 2013 curriculum material.